Longterm persistence of proteolytic activities in frass of Blattella germanica increases its allergenic potential - Erban, T; Hubert, J (Medical and veterinary entomology, 2011)
Chromogenic microplate assays in 96 wells were used to determine the stability of enzyme activity in frass of Blattella germanica (Blattodea: Blattellidae). Frass samples were exposed to controlled conditions [temperature 15-35 °C and/or 53-100% relative humidity (RH)] and to household conditions (apartment). Exposure times were 0 (control), 90, 183 and 276 days. Starch digestion and cellulolytic activities decreased during exposure. Non-specific proteolytic activities were affected by changes in selective proteolytic activities. Activities towards AAPpNA and SA(3) pNA strongly increased at 100% RH, indicating the possible influence of microorganisms growing on frass. Activities towards BApNA and ArgpNA decreased with increasing decomposition time, whereas activity towards ZRRpNA was not influenced by exposure time. The largest decrease in activities towards ArgpNA and BApNA occurred at temperatures of 15 °C, 30 °C and 35 °C and at 100% RH. Activities towards BApNA and ZRRpNA were very stable under different temperature and RH conditions; this was confirmed by findings showing that these activities were stable in the experimental apartment. In comparison with the control, activities towards ZRRpNA and BApNA after 276 days decreased by 1% and 19%, respectively. The longterm persistence of proteolytic activities in cockroach frass increases their allergenic hazard potential.
Keywords: Feces; Humidity; Peptide Hydrolases; Allergens; alergeny; Ectobiidae; zvířata; vlhkost; feces; Temperature; proteasy; Blattellidae; teplota; Animals